Novel approach for the synthesis of chiral organometallic complexes – first series of lithium 2-amino-indenide ligands bearing pendant donor groups and a unique helical bent -zirconocene - Rufanov, Konstantin A.; Titov, Ilya Yu; Lemenovskii, Dmitry A.; Krut’ko, Dmitry P.; Churakov, Andrei V. (New journal of chemistry, 2022)
A broad series of mono- and bis-2-aminoindenyl ligands, bearing pendant donor sec -amine groups was synthesized via the reaction of indan-2-one with the corresponding secondary mono- and bis -amines: 1-H from pyrrolidine, 2-H from piperidine, 3-H from morpholine, 4-H from thiomorpholine, 5-H from dibenzylamine, 6-H 2 from N , N ′-diethyldiaminopropane-1,3, 7-H 2 from piperazine, 8-H 2 from S -(+)-prolinol, 9-H from O -methyl- S -(+)-prolinol, 10-H from O -ethyl- S -(+)-prolinol and 11-H 2 from R -(-)- N -(2-anilinomethyl)-pyrrolidine. Direct metallation of 3-H, 4-H and 9-H by n BuLi led to the formation of the corresponding mono-lithiated species 3-Li, 4-Li and 9-Li. Trans -Metallation of 4-Li by ZrCl 4 led to the formation of the presumably monomeric [( η 5 -4)ZrCl 3 ] 12. Partial hydrolysis of 12 occurred after several attempts to crystallize it and led to the formation of its 1 : 1 adduct with the free ligand 4-H, [( η 5 -4)ZrCl 3 (μ- N , S -4-H)] 13. Direct metallation of 8-H 2 with [Zr(NEt 2 ) 4 ] led to the formation of a chiral bent -zirconocene with a helical structure [( η 5 ,μ- O -8) 2 Zr] 14. The molecular structure of enantiomerically pure 9-Li was determined using X-ray crystallographic studies. Alternating Li + and chelating indenyl anions are linked in infinite chains. The coordination environment of Li + consists of the η 5 -bonded five-membered ring of the indenyl fragment, the η 1 -bonded adjacent ligand and the donor sp 3 nitrogen and oxygen atoms of the chelating side chain.